2010
DOI: 10.17955/tvr.110.3.658
|View full text |Cite
|
Sign up to set email alerts
|

Is Auditory-Verbal Therapy Effective for Children with Hearing Loss?

Abstract: A longitudinal study reported positive speech and language outcomes for 29 children with hearing loss in an auditory-verbal therapy program (AVT group) (aged 2 to 6 years at start; mean PTA 79.39 dB HL) compared with a matched control group with typical hearing (TH group) at 9, 21, and 38 months after the start of the study. The current study investigates outcomes over 50 months for 19 of the original pairs of children matched for language age, receptive vocabulary, gender, and socioeconomic status. An assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 53 publications
6
23
0
3
Order By: Relevance
“…AVT is effective in promoting listening and spoken language when delivered with the parent, child and therapist in the same room. Children with hearing loss educated using AVT have developed skills in speech, 1-4 language, 1-6 self-esteem 4 , reading and mathematics 4 in line with hearing peers. However, conventional in person AVT services may not be accessible for children with hearing loss living in rural and remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…AVT is effective in promoting listening and spoken language when delivered with the parent, child and therapist in the same room. Children with hearing loss educated using AVT have developed skills in speech, 1-4 language, 1-6 self-esteem 4 , reading and mathematics 4 in line with hearing peers. However, conventional in person AVT services may not be accessible for children with hearing loss living in rural and remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study (Dornan, Hickson, Murdoch, Houston, Constantinescu, 2010) reported positive speech and language outcomes for 29 children with hearing loss in an auditory-verbal therapy program (AVT group) (aged 2 to 6 years at start; mean PTA 79.39 dB HL) compared with a matched control group with typical hearing (TH group) at 9, 21, and 38 months after the start of the study. The current study investigates outcomes over 50 months for 19 of the original pairs of children matched for language age, receptive vocabulary, gender, and socioeconomic status.…”
Section: Auditory-verbal Therapy (Avt)mentioning
confidence: 99%
“…Un estudio longitudinal, cuyo seguimiento tuvo una duración de más de 50 meses, comparó un grupo experimental de 29 niños pertenecientes a programas de TAV con pérdida auditiva severa (promedio tonos puros -PTA de 79,37 dB HL), con un grupo control de niños oyentes; los grupos fueron empalmados por edad de lenguaje, vocabulario receptivo, género y ubicación socioeconómica. Los resultados mostraron avances positivos en el habla y el lenguaje del grupo experimental y concluyeron que la TAV es efectiva para la población de niños con pérdida auditiva 21 . Otro estudio examinó la percepción del habla, el habla y el desarrollo del lenguaje en 25 niños, pertenecientes a un programa de TAV, con hipoacusia severa (promedio de tonos puros -PTA 79,37 dB HL); se realizaron evaluaciones separadas por un periodo de 21 meses.…”
Section: Reportes De La Literatura Acerca De La Tavunclassified